2023
DOI: 10.46989/001c.87755
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Plasma Cell Leukemia Outcomes Among Hospitalized Patients in the United States

Cindy Wu,
Deepa Dongarwar,
Samer Al Hadidi

Abstract: Plasma cell leukemia (PCL) is a rare, aggressive subtype of multiple myeloma (MM) with a poor prognosis. Prior studies have shown that racial disparities affect MM patients in various ways, which may affect patients’ outcomes. In this study, we aimed to investigate racial differences in hospitalization outcomes for PCL using Nationwide Inpatient Sample data. Overall, hospitalization rates for PCL tended to decrease over the past decade. Among hospitalized patients with a primary diagnosis of PCL, there was no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…We present a large single-institution body of data on PCL’s clinical, cytogenetic, and radiologic presentation and assess the impact of various therapeutic interventions on patients’ overall survival. The study included 54% Black patients (68% of female patients were Black), providing a unique opportunity to evaluate the clinical features and outcomes in a racially diverse, typically underreported population [ 20 ]. Although studies have shown that Black patients with MM have higher OS compared to White patients when receiving similar therapy, this was not extrapolated to the PCL setting; in our cohort, there was no OS difference between Black and non-Black patients [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…We present a large single-institution body of data on PCL’s clinical, cytogenetic, and radiologic presentation and assess the impact of various therapeutic interventions on patients’ overall survival. The study included 54% Black patients (68% of female patients were Black), providing a unique opportunity to evaluate the clinical features and outcomes in a racially diverse, typically underreported population [ 20 ]. Although studies have shown that Black patients with MM have higher OS compared to White patients when receiving similar therapy, this was not extrapolated to the PCL setting; in our cohort, there was no OS difference between Black and non-Black patients [ 21 ].…”
Section: Discussionmentioning
confidence: 99%